2008
DOI: 10.1007/978-3-540-68585-2_39
|View full text |Cite
|
Sign up to set email alerts
|

The 2007 AMI(DA) System for Meeting Transcription

Abstract: Abstract. Meeting transcription is one of the main tasks for large vocabulary automatic speech recognition (ASR) and is supported by several large international projects in the area. The conversational nature, the difficult acoustics, and the necessity of high quality speech transcripts for higher level processing make ASR of meeting recordings an interesting challenge. This paper describes the development and system architecture of the 2007 AMIDA meeting transcription system, the third of such systems develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 15 publications
(19 reference statements)
0
30
0
1
Order By: Relevance
“…Equally test sets for seminar style meetings from the CHIL corpora have been provided. In the past we have shown that the performance of the AMIDA systems on seminar data is strongly correlated to conference room meeting transcription [6], [12]. Hence, we have excluded such data from this paper.…”
Section: B Test Sets and Test Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Equally test sets for seminar style meetings from the CHIL corpora have been provided. In the past we have shown that the performance of the AMIDA systems on seminar data is strongly correlated to conference room meeting transcription [6], [12]. Hence, we have excluded such data from this paper.…”
Section: B Test Sets and Test Conditionsmentioning
confidence: 99%
“…The second task is segmentation and speaker clustering. In work on the RT'07 system we found a considerable mismatch between requirements for diarization and ASR [6]. ASR systems require clusters of reasonable size and can cope with segments that contain significant amounts of silence.…”
Section: B Far Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…of the system would go beyond of the scope of this paper, the interested reader is referred to [28]. Table 7 shows details for various stages in the system, from the initial decoding with unadapted models to the output of the best branch in the system.…”
Section: Performancementioning
confidence: 99%
“…Several scientific projects [18], [7] and challenges [8], [10] have been launched during the last decade targeting intelligent interfaces for indoors smart environments. Distant speech recognition (DSR) via distributed microphones is examined in most of them.…”
Section: Introductionmentioning
confidence: 99%